Socialization, Learning Creativity by Coloring Canvas Bags at SD Nahdlatul Wathan Gabus Bekasi, Srimukti Village through the Real Work Lecture (KKN) program at Bhayangkara University, Jakarta Raya - Nanda Hanifah Putri (Jurnal Abdimas Ekonomi dan Bisnis (JAmEB), 2023)
Community empowerment is essentially bringing out the potential that already exists in people or groups by offering support and increasing awareness of this potential with the aim of empowering people or groups to achieve their goals or produce effective societal changes that can change and improve socio-economic welfare. -in their environment. Community Service Lecture (KKN) activities are educational in the sense of providing learning opportunities to students outside the classroom. In Srimukti Village, KKN SEJATI 2023 will be implemented through service modalities such as outreach, learning, and creativity. The results show a good response from the community and children from the active involvement of SD Nahdlatul Wathan Srimukti.